PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PROGRAM PKM UNTUK MENINGKATKAN KAPASITAS PRODUKSI PERMEN JELLY BUAH DAN JELLY SAYURAN DI KOTA MALANG - Zainul Arifin; Istutik Istutik; Amir Kusnanto (Universitas Kadiri, 2019)
Candy is a snack that is loved by children and adolescents, because it tastes sweet, has a distinctive aroma and is affordable. Many types of candy both made from artificial ingredients and from natural ingredients. Specially soft and chewy jelly candy is much loved by young people.A businessman partner named Dian Falah Fitriyana, ST is located at Jl. Ikan Hiu II / 19 Tunjungsekar Village, Lowokwaru District, Malang City innovates by producing jelly candy from fruit raw materials (apple jelly candy and dragon fruit jelly candy) and made from vegetable raw materials (Moringa jelly candy and carrot jelly candy). As it is known that apples, dragon fruit and vegetable Moringa and carrots have many health benefits. Raw material for jelly candy is only taken from the juice and not added with preservatives.The purpose of the PKM program is to increase the production capacity of partner entrepreneurs and provide online marketing training, training and accounting assistance, so that partner entrepreneurs can make financial reports needed for a productive business.The problem of micro entrepreneurs in general is not being able to increase their production because of limited capital, which has the effect of not being able to add or replace their more modern production facilities. Marketing limitations and not doing financial records properly. The Community Partnership Program (PKM), which provides production support equipment and management improvements, will certainly increase production outputThe solutions offered by the PKM program to increase the production capacity of partner entrepreneurs are to provide juicers, sterilitators, sealers, digital scales, LPG ovens, containers, trays, containers. Meanwhile, to improve financial management and product marketing, the Team provides training and mentoring in accounting and marketing training. It is expected that partner entrepreneurs are able to make financial records (cash flow) and market their products through internet marketing.Partner entrepreneurs with the help of new equipment from the PKM program are targeting production to increase by 50% to 100%. This optimistic target is achieved due to juice, sterilitators, chopper machines, large ovens and more modern production facilities, entrepreneurs will be able to serve the demands of more consumers.The progress of PKM program activities has reached 70% of the target, but there are still activities to assist in making financial reporting and online marketing.